Effect of combined uphill-downhill sprint training on kinematics and maximum running speed in experienced sprinters - Paradisis, G. P.; Bissas, A.; Cooke, C. B.; Brown, L.; Slawinski, J. (International Journal of Sports Science and Coaching, 2015)
This study examined the effects of sprint running training on sloping surfaces (3°) in experienced sprinters using selected kinematic variables. Twelve experienced sprinters were randomly allocated to two training groups (combined uphill-downhill and horizontal). Pre- and post-training tests were performed to examine the effects of six weeks of training on maximum running speed, step rate, step length, step time, contact time, braking and propulsive phase of contact time, flight time and selected postural characteristics during a step cycle in the final steps of a 35m sprint test. In the combined uphill-downhill training group, maximum running speed was substantially greater (from 9.08 ± 0.90 m s-1 to 9.51 ± 0.62 m s-1; p <0.05) after training by 4.8%; step rate, contact time, step time and concentric phase was not modified. There were no significant changes in maximal speed or sprint kinematics in the horizontal training group. Overall, the posture characteristics did not change with training. The combined uphill-downhill training method was substantially more effective in improving the maximum running speed in experienced sprinters than a traditional horizontal training method. ABSTRACT FROM AUTHOR